C-arm computed tomography and volume perfusion computed tomography (VPCT)-based assessment of blood volume changes in hepatocellular carcinoma in prediction of midterm tumor response to transarterial chemoembolization: a single center retrospective trial. Issue 1 (December 2016) - Syha, Roland; Gatidis, Sergios; Grözinger, Gerd; Grosse, Ulrich; Maurer, Michael; Zender, Lars; Horger, Marius; Nikolaou, Konstantin; Ketelsen, Dominik
Abstract Background This study aims to evaluate immediate changes in perfusion parameters in hepatocellular carcinoma (HCC) to transarterial chemoembolization (TACE) in C-arm computed tomography (CT) and volume perfusion CT (VPCT) and prediction of midterm tumor response. Methods Twenty-five patients (median age 66, range 61 to 75 years) with 62 HCC lesions undergoing TACE received immediate pre- and post-interventional assessment by C-arm CT and VPCT. Cross-sectional imaging was analyzed at baseline and approximately 12 weeks after TACE according to modified RECIST criteria. Outcome was defined as objective response (OR, > 30 % reduction of viable tumor) or non-OR. Perfusion parameters were evaluated in C-arm CT [parenchymal blood volume (PBV)] and VPCT [blood volume (BV) and blood flow (BF)]. Ratios of perfusion parameters before and after TACE within the tumor and the non-affected liver parenchyma were calculated. Results Correlation between tumor PBV and BV revealed a moderate correlation (rho = 0.45, p = 0.005). In non-affected liver parenchyma, a significant decrease in PBV was seen, compared to a significant increase in BF and BV. Perfusion ratios in HCC lesions were significantly (p < 0.05) increased in OR group compared to non-OR patients in C-arm CT and VPCT: PBV ratio (0.95 (0.06) to 0.67 (0.38), BV ratio 0.63 (0.34) to 0.15 (0.6), and BF ratio 0.6 (0.32) to 0.22 (0.51). Logistic regression including PBV and BF allowed prediction of OR (sensitivity 88 %/specificity of 83 %). Conclusions Perfusion parameters acquired by C-arm CT and VPCT cannot simply be substituted by each other, but show similar capability in prediction of midterm tumor response.